2010
DOI: 10.1021/ol101596s
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Efficient Preparation of 2,5-Disubstituted Oxazoles via a Metal-Free-Catalyzed Cascade Cyclization

Abstract: A practical and simple synthesis of 2,5-disubstituted oxazoles was developed via an iodine-catalyzed tandem oxidative cyclization. A wide range of common commercial aromatic aldehydes can be used as reaction substrates, which displayed excellent functional group compatibility in this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…This indicated that the reaction should undergo a radical pathway. Based on the results described above and previous reports [27,28,45,46], a plausible mechanism for this decarboxylative cyclization was proposed as follows (Scheme 2). Initially, compound A, formed by the substitution reaction of 1a with 2a, which can be transformed following two pathways: (a) I + , generated by the oxidation of iodine, could oxidize A to radical intermediate B, which eliminates one molecular of CO 2 to generate radical C, which is further oxidized to imine D or its isomer E. Subsequently, F is obtained by intramolecular nucleophilic addition of E. Finally, the desired product (3a) is given by deprotonation and oxidation of F; (b) G is formed from the oxidation of A.…”
Section: Research Of the Reaction Mechanismmentioning
confidence: 88%
“…This indicated that the reaction should undergo a radical pathway. Based on the results described above and previous reports [27,28,45,46], a plausible mechanism for this decarboxylative cyclization was proposed as follows (Scheme 2). Initially, compound A, formed by the substitution reaction of 1a with 2a, which can be transformed following two pathways: (a) I + , generated by the oxidation of iodine, could oxidize A to radical intermediate B, which eliminates one molecular of CO 2 to generate radical C, which is further oxidized to imine D or its isomer E. Subsequently, F is obtained by intramolecular nucleophilic addition of E. Finally, the desired product (3a) is given by deprotonation and oxidation of F; (b) G is formed from the oxidation of A.…”
Section: Research Of the Reaction Mechanismmentioning
confidence: 88%
“…: 73 °C (lit: 72-73 °C). 38 1 H NMR (400 MHz, CDCl 3 ) δ: 7.97 (d, J = 8.0 Hz, 2H), 7.66 (d, J = 7.8 Hz, 2H), 7.41-7.37 (ovrlp, 3H), 7.28 (t, J = 7.6 Hz, 1H), 7.24 (d, J = 8.0 Hz, 2H), 2.36 (s, 3H). 13 C NMR (100 MHz, CDCl 3 ) δ: 161.3, 150.9, 140.6, 129.5, 128.9, 128.3, 128.1, 126.2, 124.8, 124.1, 123.3, 21.5.…”
Section: Methodsmentioning
confidence: 99%
“…: 84-85 °C (lit: 81-82 °C). 38 1 H NMR (400 MHz, CDCl 3 ) δ: 8.04 (dd, 3 J HH = 8.8 Hz, 4 J HF = 5.2 Hz, 2H), 7.64 (d, 3 J HH = 7.2 Hz, 2H), 7.41-7.37 (ovrlp, 3H), 7.29 (t, 3 J HH = 7.2 Hz, 1H), 7.11 (dd, 3 J HH = 8.8 Hz, 3 J HF = 8.8 Hz, 2H). 13 C NMR (100 MHz, CDCl 3 ) δ: 164.0 (d, J CF = 249.4 Hz), 160.3, 151.3, 128.9, 128.5, 128.3 (d, 3 J CF = 8.6 Hz), 127.9, 124.1, 123.8 (d, 4 J CF = 3.0 Hz), 123.4, 116.0 (d, 2 J CF = 21.9 Hz).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of compound is very rare in the natural world. Owing to their attractive structures, there have been total syntheses of some of the members of DPO [10][11][12]. Herein, we describe the isolation and structure elucidation of gymnotheoxazoles A (1) and B (2), and their cytotoxicity against A549 cell.…”
Section: Introductionmentioning
confidence: 99%